Childhood Adversity and Traumatic Disorders: A self-report and Danish linkage study - Murphy, Siobhan; Shevlin, Mark; Elklit, Ask; Christoffersen, Mogens (International Journal of Population Data Science, 2018)
Background Accurate assessment of childhood adversity is fundamental in understanding risk and resilient factors that can inform appropriate intervention and prevention strategies. Different statistical and methodological approaches (e.g., prospective, selfreported data) have been used to assess pathways and outcomes associated with childhood adversity, however, each is limited in a number of ways. Objectives Linking administrative data to population-based studies provides a powerful tool to overcome some of the challenges in trauma research and permits the estimation of temporally ordered models of risk. The current study seeks to assess the effect of childhood adversity on a diagnosis of traumatic disorder (TD). Methods Data were collected from a Danish national study in 2008/2009. A sample of 4,718 young adults were randomly selected from the birth cohort of children born in 1984. Structured interviews were conducted on 2,980 participants. This data was then linked with parental data (including 4 years prior to birth of child) and a ICD 10 diagnosis of a TD using information from the Danish registries. Findings Hierarchical regression analysis was used to examine parental risk factors, self-reported child maltreatment, experiencing violence in young adulthood and risk of a TD diagnosis at age 28. Findings indicated the dominant factor associated with TD was self-reported PTSD symptoms at age 24 (OR =3.82); followed by a parental mental health diagnosis (OR = 2.80). Being of female gender (OR = 2.42) and experiencing violence in young adulthood (OR = 1.94) also increased risk of a TD diagnosis. Conclusion This study highlights the benefits of incorporating administrative data with self-report data to provide a more nuanced understanding of childhood adversity across different developmental stages. These findings have important conceptual and methodological implications and may be useful in informing future trauma studies.